Study of antispasmodic action of Lavandula angustifolia Mill hydroalcoholic extract on rat ileum - Hassan Sadraei; Gholamreza Asghari; Mojtaba Rahmati (Shahrekord University of Medical Sciences, 2019)
Introduction: Lavender (Lavandula angustifolia Mill) is a herbal medicine widely used for gastrointestinal (GI) disorders. However, its pharmacological action on isolated ileum has not been studied. In this research effect of hydroalcoholic extract of L. angustifolia on isolate ileum contractions was studies and compared with loperamide. Methods: Hydroalcoholic extract of the plant was prepared by percolation method. The total flavonoid contents were assessed by colorimetric technique. A portion of rat ileum was suspended in an organ bath containing Tyrode's solution. The tissue was kept under 1 g tension at 37°C and continuously gassed with O2. The tissue was stimulated with KCl (80 mM), acetylcholine (ACh, 2 μM) and electrical field stimulation (EFS). Effect of the L. angustifolia extract was studied on ileum contractions and compared with that of loperamide. Results: The yield of hydroalcoholic extract was 17% with total flavonoid content of 185 μg/mL in the stock solution. Loperamide in concentration dependent manner inhibited ileum contractile response to KCl, ACh and EFS. Hydroalcoholic extract of L. angustifolia (8-512 μg/mL) concentration dependently inhibited ileum contraction induced by KCl (IC50 = 88 ± 21 μg/mL), ACh (IC50 = 119 ± 251 μg/mL) and EFS (IC50 = 87 ± 33 μg/mL). The vehicle had no significant effect on ileum contractions. Conclusion: From this study it was concluded that L. angustifolia extract at microgram concentration shows an inhibitory effect on rat ileum smooth muscle. Therefore, isolation and identification of active ingredients are recommended.